Answer:
Step-by-step explanation:
Discussion
This should be answered with the mean. The lower the mean, the lower the score it took to get the mean. So B is the answer.
Answer:
- y = 2x + 3
- y = -6x
- y = -x + 2
- y = 2x - 7
Step-by-step explanation:
<u>Slope-intercept form:</u>
<em>Hint. if we have x = 0, then the y-coordinate is the same as b</em>
<u>Slope</u>
33.
- m = (9 -(-3))/(3 - (-3)) = 12/6 = 2
- b = 3 as per table (0, 3)
34.
- m = (0-12)/(0 - (-2)) = -12/2 = -6
- b = 0, as per table (0, 0)
35.
- m = (2 - (-2))/(0 - 4) = 4/-4 = -1
- b = 2, as per table (0, 2)
36.
- m = (-5 - (-1))/ (1 -3) = -4/-2 = 2
Using point (3, -1)
- -1 = 2*3 + b
- b= -1 - 6= - 7
Answer:
-1
Step-by-step explanation:
substitute x for 6 and y for 1
which will be 6-1+6
using BODMAS
6-(1+6)
6-7= -1
THE EQUATION TO THIS PROBLEM IS y=2x+12